Mapping polyclonal antibody responses to bacterial infection using next generation phage display - Naqid, Ibrahim A.; Owen, Jonathan P.; Maddison, Ben C.; Spiliotopoulos, Anastasios; Emes, Richard D.; Warry, Andrew; Tchorzewska, Monika; Martelli, Francesca; Gosling, Rebecca J.; Davies, Robert H.; La Ragione, Roberto M.; Gough, Kevin C. (Nature Publishing Group, 2016)
Mapping polyclonal antibody responses to infectious diseases to identify individual epitopes has the potential to underpin the development of novel serological assays and vaccines. Here, phage-peptide library panning coupled with screening using next generation sequencing was used to map antibody responses to bacterial infections. In the first instance, pigs experimentally infected with Salmonella enterica serovar Typhimurium was investigated. IgG samples from twelve infected pigs were probed in parallel and phage binding compared to that with equivalent IgG from pre-infected animals. Seventy- seven peptide mimotopes were enriched specifically against sera from multiple infected animals. Twenty-seven of these peptides were tested in ELISA and twenty-two were highly discriminatory for sera taken from pigs post-infection (P < 0.05) indicating that these peptides are mimicking epitopes from the bacteria. In order to further test this methodology, it was applied to differentiate antibody responses in poultry to infections with distinct serovars of Salmonella enterica. Twenty-seven peptides were identified as being enriched specifically against IgY from multiple animals infected with S. Enteritidis compared to those infected with S. Hadar. Nine of fifteen peptides tested in ELISA were highly discriminatory for IgY following S. Enteritidis infection (p < 0.05) compared to infections with S. Hadar or S. Typhimurium.